Akad Tijarah Dalam Praktek Di Lembaga Keuangan Mikro Syariah - BMT - Nandang Ihwanudin; Handri Handri; Deden Gandana Madjakusumah; M Munir Asrori (LPMP Imperium, 2020)
Purpose- Akad tijarah as a form of trade agreement has several types, in which needs to be adjusted to each necessity. It is important for related parties to understand what and how akad ijarah works. This article analyses how far the contribution of an Islamic microfinance institution (LKMS) nowadays, considering there are nash (Al-Qur’an and Al-Hadits) and also fatwa the national sharia council (DSN) MUI. Methods- Case studies and literature reviews are used to evaluate sharia business practices in BMT. Findings- Sharia microfinance institutions, in this case, BMT TUMANG, have carried out sharia principles in practice, especially for tijarah agreements with documents in the form of SOM and SOP as well as financing contracts (agreements), both in the principle of sale and profit-sharing. Implications/Limitations- This study is limited to one branch of the BMT so it cannot describe the overall practice carried out in other regions.